UNDERSTANDING ECONOMIC CRIMES: UNVEILING THE WORLD OF WHITE-COLLAR OFFENSES - Hamja, Hamja (Jurnal Pembaharuan Hukum, 2024)
White-collar crime encompasses a broad spectrum of illicit activities conducted within the boundaries of a legitimate profession or financial system. The purpose of this study is to critically examine and analyze the ethical dimensions of economic offenses, seeking to foster a deeper understanding of the moral responsibilities inherent in positions of power and influence. Normative and empirical-juridical research methods are used to comprehensively investigate the phenomenon of white-collar crime. The results of this study are that white-collar crimes are usually committed by individuals who hold positions of authority, respect, and expertise in society. High-ranking officials are entrusted with significant responsibilities by the public to lead and fulfill their duties in an ethical and legitimate manner. officials abuse their power and privileges, acting in ways that undermine public trust and negatively impact the welfare of the state. In terms of criminal law enforcement, white-collar crime often manifests as malfeasance committed by individuals within the government bureaucracy or in collaboration with others. The consequences of such actions, especially in cases of corruption, can cause serious losses to the state's finances and are considered violations of the law, which are punishable under the provisions of the law governing the offense or crime.